Dendritic Cells and Immunogenic Cancer Cell Death: A Combination for Improving Antitumor Immunity - María Julia Lamberti; Annunziata Nigro; Fátima María Mentucci; Natalia Belén Rumie Vittar; Vincenzo Casolaro; Jessica Dal Col (Pharmaceutics, 2020)
The safety and feasibility of dendritic cell (DC)-based immunotherapies in cancer management have been well documented after more than twenty-five years of experimentation, and, by now, undeniably accepted. On the other hand, it is equally evident that DC-based vaccination as monotherapy did not achieve the clinical benefits that were predicted in a number of promising preclinical studies. The current availability of several immune modulatory and targeting approaches opens the way to many potential therapeutic combinations. In particular, the evidence that the immune-related effects that are elicited by immunogenic cell death (ICD)-inducing therapies are strictly associated with DC engagement and activation strongly support the combination of ICD-inducing and DC-based immunotherapies. In this review, we examine the data in recent studies employing tumor cells, killed through ICD induction, in the formulation of anticancer DC-based vaccines. In addition, we discuss the opportunity to combine pharmacologic or physical therapeutic approaches that can promote ICD in vivo with in situ DC vaccination.